Seller side HR perspectives during M&A deals: The journey from "intent" to "deal fruition". Issue 6 (13th June 2016) - Pathak, Atul Arun
Abstract : Purpose: This paper aims to focus on the HR issues that seller organizations face during the pre-deal stage of mergers and acquisitions (M&A). It recommends the HR strategies that strategies that seller-side organizations need to adopt to improve their chances of successful M&A. Design/methodology/approach: The paper explores the HR-related issues faced by seller-side organizations. It highlights the key dilemmas and challenges involved at this stage of M&A deals. It recommends the HR strategies that seller companies can follow during the pre-deal stage of an M&A deal. Findings: What the seller's HR leaders do (and do not do) during the run up to an M&A deal can significantly affect the success of the post-deal integration and future success of the combined firm. During the pre-deal phase of an M&A journey, HR leaders face a range of dilemmas. They have to decide whether to maintain business as usual or change their HR strategy, decide when to hide information and when (and what) to communicate internally and also have to prepare the seller organization for an HR audit by the buyer firm. Practical implications: HR leaders in seller organizations need to continue to increase the value of the organization by continually aligning the HR strategy to the organization's overall corporate and business strategy. During the early stages of the deal, they have to camouflage certain confidential details. When the deal is at an advanced stage, HR leaders have to communicate extensively with employees about the deal. They need to ensure that the organization is prepared for an HR audit by prospective buyers. However, they also have to ensure that the reasons for the seller organization's success are not revealed fully and prematurely. Social implications: It concedes that during an M&A deal, the HR leaders of a seller organization need to balance the interests of multiple stakeholders. These include the firm's owners, top managers, employees and key customers. Those who are unable to do this effectively and consistently may end up harming the interest of the seller organization during an M&A deal. Originality/value: The paper considers the highly dynamic e-commerce industry in India. It is a sector that is seeing rapid growth. Many new players are entering the market and the battle is for size and scale. In such a scenario, companies such as Flipkart are using the M&A route to scale up inorganically. Recently, Flipkart acquired Myntra, a strong player in the online retailing of fashion garments. The paper provides insights in to the challenges faced by the seller organization's HR managers during the pre-deal stage of M&A transactions and recommends strategies that they should follow.